Introducing and Utilizing E-Reading Tools for Junior High School Students through the Read Along by Google Application : Pengenalan dan Pemanfaatan E-Reading Tools untuk Siswa SMP melalui Aplikasi Read Along by Google - Eva Meidi Kulsum (Institut Riset dan Publikasi Indonesia, 2025)
The development of digital technology presents significant opportunities to enhance students' literacy, particularly in learning English. However, the integration of technology in school environments remains limited, and many students have not yet utilized digital tools as productive learning media. This Community Service Program (PKM) aimed to increase junior high school students’ interest and reading comprehension in English by introducing the Read Along by Google application. The program was conducted at MTs As-Syifa, West Bandung Regency, involving 50 students as participants. The method employed was the Asset-Based Community Development (ABCD) approach through interactive seminars, application simulations, and reflective discussions. The results showed high enthusiasm among students in using the Read Along application, with positive responses toward its interactive features. Besides boosting reading motivation, the activity also encouraged students to integrate technology into their daily learning habits. Therefore, the asset-based and technology-oriented approach proved effective in strengthening digital literacy and supporting English learning at the junior high school level.